Living Water An interdisciplinary exploration of water as a theological theme - Rheeder, Riaan (Reformed Theology in Africa Series, 2023)
Water will undoubtedly become an ever more crucial locus of academic reflection, as Christiana Peppard's concern that "wars of the future will be fought over water, not oil" (2014) stresses. Increasing water shortages worldwide and global warming of water, in particular the salt water of the oceans, beg further reflection, from natural and agricultural sciences, the legal field, and also from theology. As a basic human right, water is also closely connected to peace and justice issues. This book is an interdisciplinary undertaking looking at water as a theological symbol in the fields of theology, natural and agricultural sciences, and law. Providing reflections from a variety of disciplines within theology, as well as from other disciplines such as natural sciences and law from the South African context, this book makes a valuable contribution to knowledge in this field.